2019
DOI: 10.20885/jeki.vol5.iss2.art6
|View full text |Cite
|
Sign up to set email alerts
|

The society’s perceptions on the use of fintech services in sharia financial institutions

Abstract: In the development of industrial revolution 4.0, sharia financial institutions keep improving their product innovation through the use of financial technology (fintech). Through development and innovation, society is expected to keep up to date with the current financial services. This research aims to investigate how the interest in using sharia services affected by several factors, such as convenience, benefits, attitude, and suitability. This research uses a descriptive quantitative method through multi-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
10
1
1
Order By: Relevance
“…In addition, problems such as fraud, hacking, identity theft, and other cybercrimes are also the main reasons that reduce the trust of many people to use FinTech (Niswah et al, 2019). However, this study supports the result of a previous study conducted by (Niswah et al, 2019;Purwantini et al, 2020) and contrasts to research findings by Yuspita et al (2019).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In addition, problems such as fraud, hacking, identity theft, and other cybercrimes are also the main reasons that reduce the trust of many people to use FinTech (Niswah et al, 2019). However, this study supports the result of a previous study conducted by (Niswah et al, 2019;Purwantini et al, 2020) and contrasts to research findings by Yuspita et al (2019).…”
Section: Discussioncontrasting
confidence: 79%
“…Kasri & Chaerunnisa (2020) found that attitude toward behavior has a positive significant effect on the intention of millennials in Indonesia to donate cash money digitally. The same thing is also found in empirical research conducted by Yuspita et al (2019) and Darmansyah et al (2020) that tested people's perceptions of using FinTech services provided by Islamic financial institutions found that ATB has a positive influence.…”
Section: Attitude Towards Behaviorsupporting
confidence: 70%
See 1 more Smart Citation
“…These results support the previous findings of Chuang, Liu, and Kao [13] who found brand and service trust have a positive impact on people's attitudes to using FinTech services. In another study, Yuspita et al [14] found an impact of perceived ease and interest, perceived benefits and interest, and attitude and interest towards people's intention to use these services. This means that the convenience and benefits offered attract public interest in addition to the influence of other people who have already used the service which attracts the public as well.…”
Section: Introductionmentioning
confidence: 96%
“…;Rabbani & Thalassinos (2020);Yuspita, & Zahra (2019);Barata (2019);Firmansyah & Anwar, (2019). Financial literacy and value in sharia fintech in Indonesia has been done by Abdillah Ubaidi (2017) about the relationship between the phenomenon of information technology development with a financial institution, index of financial literacy and inclusion and benefit of Fintech in Indonesia with the SOR (Stimulus-Organism-Response) Model.…”
mentioning
confidence: 99%